Nafion based semi-interpenetrating polymer network membranes from a cross-linkable SPAEK and a fluorinated epoxy resin for DMFCs. (20th November 2019) - Ru, Chunyu; Gu, Yiyang; Duan, Yuting; Na, Hui; Zhao, Chengji
Abstract: A Nafion based blending PEM with a thinner thickness but enhanced methanol resistance was prepared by introducing a semi-interpenetrating polymer network (semi-IPN) between Nafion matrix and blender. A side-chain-type sulfonated poly(arylene ether ketone) (SNF-PAEK) blender with hydroxyl groups was designed to be cross-linked by a fluorinated epoxy resin monomer (fEO) to form the semi-IPN in blending membranes (S@N/fEO). The S@N/fEO-6 exhibits enhanced proton conductivity (0.198 S cm −1 ) due to the aggregated ionic clusters in SNF-PAEK. Besides, the blenders caused a rearrangement in microstructure, leading to a shorter ionic clusters distance and facilitating the proton conduction, proved by TEM and SAXS. Furthermore, all S@N/fEO membranes show satisfactory dimensional stability and suppressed methanol crossover (methanol permeability of 1.34 × 10 −6 cm 2 s −1 ) because the semi-IPN restricts the molecular segments movement and hinders methanol passing through. Compared with Nafion 212, S@N/fEO-6 membrane performs superior single cell efficiency of 180.9 mW cm −2, almost 29% increase. Electrochemical impedance spectroscopy was used to further study the behavior of membranes, and S@N/fEO-6 was found to possess the lowest mass transfer resistance contributing to the best single cell performance. Thus, Nafion-based semi-IPN membrane is proved to improve properties significantly and have potential to be applied in DMFC.